The Effect of Line Webtoon in Improving Vocabulary Mastery - Mayang Sari; Muchsin Muchsin; Faudi Faudi (English LAnguage Study and TEaching, 2023)
This study aims to find out whether the students at SMAN 16 Banda Aceh who are taught English vocabulary by using line Webtoon get higher score compared to those who are not taught by using line Webtoon. This research used a quantitative approach with pre-experimental design, one group pre-test and post-test. The population in this study were 20 of class XI (IPA), and the total sample was 20 students consisting of one class, consisting of 11 males and 9 females. The data was collected through tests, namely a multiple choice question test. The results of data analysis showed that the average pretest score of students was 38.00. While the average score of the students' post-test was 77.25. The increase obtained from the average score of the pre-test and post-test was 39.25. In addition, the SPSS results show that a significant value (sig-2 tailed) of 0.00 is less than 0.05 (0.000.05), which means that Ho is rejected and HÃ¢â€šÂ is accepted. Thus, it can be concluded that there is a significant difference between students who are taught vocabulary using the line Webtoon get a higher score than students who are not taught using the line Webtoon. It is concluded that line Webtoon has an effect on improving studentsÃ¢â‚¬â„¢ vocabulary mastery.